Effect of Cryogenic Treatment on Hardness Value and Microstructure of Medium Carbon Steel - Tsamroh, Dewi Izzatus; Dika, Johan Wayan; Yazirin, Cepi; Sasongko, Muhammad Ilman Nur; Prasetiyo, Ardianto (Journal of Mechanical Engineering, Science, and Innovation, 2024)
Medium carbon steel is a kind of material that is usually used in manufacturing axles, gears and shaft. The application of medium carbon steel to axles, gears and shaft requires high hardness on the surface, but high ductility at the core. The mechanical properties of this material can be improved through a heat treatment process. However, in mass production there is obstacles, which is the uneven hardness on the entire surface, thus, it does not meet the hardness standards set as a commercial product. Therefore, cryogenic treatment was added which aimed to maintain the hardness value of the material after heat treatment. The material used in this research was S45C steel. The heat treatment conducted to increase the hardness of S45C steel was hardening followed by tempering. Hardening was carried out at a temperature of 900 with a holding time of 45 minutes, followed by rapid cooling (quenching) using dromus oil as a medium. Tempering was carried out at 450 for 15 minutes. Cryogenic treatment was carried out at -190 for 1 hour. The research results showed that the highest hardness was obtained in specimens with hardening-quenching treatment followed by cryogenics with a hardness value of 35 HRC (core) and 35.8 HRC (surface). The hardness test results were in line with the microstructure test results., where the microstructure of specimens that had hardening-quenching treatment followed by cryogenics were dominated by pearlite, thus the hardness value were high.